Relapses and disease-modifying drug treatment in pregnancy and live birth in US women with MS. (23rd October 2018) - Houtchens, Maria K.; Edwards, Natalie C.; Phillips, Amy L.
Abstract : Objective: To evaluate relapse rates and disease-modifying drug (DMD) treatment in US women with multiple sclerosis (MS) and a live birth. Methods: This retrospective administrative claims database study used US commercial health plan data from women with MS and a live birth from January 1, 2006, to June 30, 2015. Relapses and DMD treatment were evaluated 1-year prepregnancy, during pregnancy, during puerperium (6 weeks postpregnancy), and 1-year postpregnancy. Relapse was defined as MS-related hospitalization, emergency room visit, or outpatient visit with corticosteroid prescription within 7 days. Generalized estimating equation models for longitudinal data tested for differences between prepregnancy vs the other time periods. Results: A total of 2, 158 patients were eligible. The odds of relapse declined during pregnancy (odds ratio [OR] 0.623, 95% confidence interval [CI] 0.521–0.744; p < 0.0001), increased during puerperium (OR 1.710, 95% CI 1.358–2.152; p < 0.0001), and ended at a higher level during the last 3 postpartum quarters (OR 1.216, 95% CI 1.052–1.406; p = 0.0081). The proportion of women with DMD treatment was rather low overall: approximately 20% prepregnancy, bottoming to 1.9% during the second trimester, and peaking at 25.5% 9 to 12 months postpartum. DMD treatment declined significantly during pregnancy (OR 0.171, 95% CI 0.144–0.203; p < 0.0001), remained lower during puerperium (OR 0.361, 95% CI 0.312–0.418; p < 0.0001), and ended at a higher level during the last 3 postpartum quarters (OR 1.259, 95% CI 1.156–1.371; p < 0.0001). Conclusions: The rate of MS relapse decreased during pregnancy, increased 6 months postpartum, and decreased 6 to 12 months postpartum. DMD treatment was uncommon in the year before pregnancy, further decreased immediately prepregnancy and during pregnancy, and increased postpartum.